CRYOPRESERVATION OF Fraxinus excelsior L. EMBRYOGENIC CALLUS BY ONE-STEP FREEZING AND SLOW COOLING TECHNIQUES - Ozudogru, E. A.; Capuana, M.; Kaya, E.; Panis, B.; Lambardi, M. (Cryo Letters, 2010)
An efficient cryopreservation protocol for the safe storage of Fraxinus excelsior L. embryogenic callus cultures is reported. The cryopreservation methods tested included one-step freezing by means of (i) encapsulation-vitrification; or (ii) encapsulation-dehydration; and (iii) slow cooling using the Nalgene Freezing container, Mr Frosty (R), which produces a temperature decrease of about 1 degrees C min(-1) when placed in a -70 degrees C freezer. None of the one-step freezing techniques was effective for cryopreservation of encapsulated callus masses, irrespective of the cryoprotective treatment applied, i.e., treatment with the PVS2 vitrification solution or physical dehydration with silica gel before direct immersion in liquid nitrogen. On the contrary, when a slow cooling protocol was applied to embryogenic callus which had been pretreated for 60 min with a 210 g l(-1) (0.61 M) sucrose-7.5% DMSO cryoprotective solution, up to about 1.3 g per Petri dish of proliferating callus was observed 42 days after recovery from liquid nitrogen, and cultures were able to produce somatic embryos 8 weeks after transfer to semi-solid medium. TTC staining of callus cultures provided a fast evaluation of culture viability.
Keywords: common ash; encapsulation-dehydration; encapsulation-vitrification; slow cooling; somatic embryogenesis